Local excision and radical excision for rectal gastrointestinal stromal tumors: a meta-analysis protocol - Luo, Wenjun; Liu, Chunyu; Han, Luyin; Zhang, Haidong; Shen, Chaoyong; Yin, Xiaonan; Zhao, Zhou; Mu, Mingchun; Jiang, Tianxiang; Cai, Zhaolun; Zhang, Bo (Frontiers in Oncology, 2023)
Background: To date, several studies have compared the surgical and oncological outcomes of local excision (LE) and radical excision (RE) for rectal gastrointestinal stromal tumors (GISTs), but some have limited numbers of small series. This protocol outlines the planned scope and methods for a systematic review and meta-analysis that will compare the surgical and oncological outcomes of LE and RE in patients with rectal GISTs.Methods: This protocol is presented in accordance with the PRISMA-P guideline. PubMed, Embase, Web of Science, Cochrane Library and Wanfang database will be systematically searched. Furthermore, reference lists of all included articles will be screened manually to add other eligible studies. We will include randomized controlled trials (RCTs) and non-randomized studies (NRS) in this study. The primary outcomes evaluated will be R0 resection rate and 2 disease-free survival, while the secondary outcomes will contain overall survival, length of stay, tumor rupture rate and complications. Two reviewers will independently screen and select studies, extract data from the included studies, and assess the risk of bias of the included studies.Preplanned subgroup analyses and sensitivity analyses are detailed within this protocol. The strength of the body of evidence will be assessed using GRADE Discussion: This review and meta-analysis will provide a comprehensive evaluation of the current evidence concerning the application of LE and RE in patients with rectal GISTs. The findings from this review will serve as a foundation for future research and emphasize the implications for clinical practice.